Method and system for providing services for wireless data calls - Ram Dantu; Patel, Pulin; Patel, Pravir; Garbuz, Alexander; Miernik, Jerzy; Patel, Achal; Holur, Balaji (Cisco Technology Inc, 2007)
A method and system for providing services for wireless data calls includes monitoring a wireless data call for a predefined event associated with a service for the wireless data call. The service is initiated for the wireless data call in response to detecting the predefined event for the data call. The predefined event may comprise a uniform resource locator (URL) match or change, excess use of transmission or time resources, a location change of a mobile device for the wireless data call, a network event, or a combination of any or all suitable events.
Keywords: call; data; network; service; wireless

Method and system for configuring wireless routers and networks - Patel, Pulin; Choksi, Ojas; Davidson, Kenneth; Ram Dantu (Cisco Technology Inc, 2006)
A method and system for configuring a wireless router and a wireless communications network includes establishing connectivity between a wireless router and at least one wireline router. Connectivity between the wireless router and a plurality of neighboring wireless routers is established through the wireline router. The wireless router is configured based on information exchanged with the neighboring wireless routers through the wireline router.
Keywords: parameters; router; state; step; wireless

Wireless router and method for processing traffic in a wireless communications network - Ram Dantu; Patel, Pulin; Choksi, Ojas; Patel, Achal; Ali, Mohammad; Miernik, Jerzy; Holur, Balajl (Cisco Technology Inc, 2006)
A wireless communications network includes a wireless-specific router topology layer that connects cellular sites to a wireline topology. The wireless-specific router topology provides a distributed architecture in which call processing including call setup, resource preservation, air bandwidth allocation, switching, soft handoff, and micromobility is performed at the cell level. The wireless routers are technology independent to support various cellular technologies. The wireless router may include a first interface operable to communicate wireless packets for a call with a remote device and a second interface operable to communicate wireline packets for the call with the wireline network. A traffic controller is coupled to the first and second interfaces and operable to convert traffic between the wireless and wireline packets and to route packets to a destination mobile or wireline device. A selection and distribution unit is operable to select and distribute traffic to support soft handoff for calls in the wireless communications network.
Keywords: network; router; routers; traffic; wireless